Neutrophil-to-albumin ratio: a novel predictor of osteoporosis in rheumatoid arthritis - Zhang, Yifang; He, Zhongyu; Li, Kaiqiang; Wu, Qiuping; Wang, Shigang; Liu, Minying; Liu, Qingping; Xu, Qiang; Kong, Xiangying; Lin, Changsong (Frontiers in Immunology, 2025)
BackgroundOsteoporosis (OP) frequently coexists with rheumatoid arthritis (RA), but validated predictors of early risk are not extensively studied. This study seeks to examine the relationship between the neutrophil percentage-to-albumin ratio (NPAR) and the likelihood of developing RA-related OP(RA-OP).MethodsAfter investigating the relationship between the NPAR and RA-OP in the clinical retrospective study, we further validated this association using data from the National Health and Nutrition Examination Survey (NHANES) database (2005-2020 cycles). This retrospective study enrolled 718 RA patients from the Rheumatology Department of the First Affiliated Hospital of Guangzhou University of Chinese Medicine between January 2020 and December 2024. Patients were categorized into low-NPAR (<1.7598) and high-NPAR (≥1.7598) groups based on the median NPAR. Extracted clinical data encompassed demographic characteristics, comorbidities, serological markers, and other laboratory parameters. Preliminary univariate and multivariate logistic regression analyses assessed potential associations between NPAR and RA-OP, multi-model adjusted logistic regression was subsequently applied to evaluate the independent association, subgroup analyses examined consistency across demographic and clinical strata, Receiver operating characteristic (ROC) curve analysis assessed NPAR’s diagnostic performance, and then Restricted cubic splines (RCS) visualized potential non-linear relationships. Finally using the identical statistical framework, we validated findings within the NHANES cohort.ResultsThe high-NPAR group exhibited significantly higher OP incidence than the low-NPAR group (39.0% vs. 26.5%; P<0.001). After full adjustment (Model 4), NPAR remained independently associated with increased RA-OP risk as a categorical variable (high vs. low NPAR: adjusted OR = 1.70 (95%CI: 1.01 2.88); P = 0.049). Subgroup analyses demonstrated no significant interaction effects (P-interaction>0.05) except for disease duration. The ROC curve showed an Area Under the Curve(AUC) of 0.58 (95%CI: 0.53 0.63) and NPAR cut-off of 1.886. The covariate-adjusted RCS indicated a linear dose-response relationship (P overall=0.033; P nonlinearity=0.168). NHANES cohort analysis independently validated both the NPAR-RA-OP association and its linear characteristic.ConclusionNPAR, serving as a novel composite biomarker integrating neutrophil-mediated inflammation and nutritional status (via albumin), independently predicts OP risk in RA. Its derivation from routine clinical parameters renders NPAR a readily deployable, cost-effective tool for OP risk stratification in clinical practice.